The variability of isokinetic ankle strength is different in healthy older men and women (Clinics, 2022)
Context: In the elderly, weak lower limb muscles impair functional tasks' performance.Objective: To evaluate the healthy elderly's ankle dorsiflexion and plantarflexion maximum torque and its variability in two sets of 5 RM isokinetics evaluation.Method: 50 women (68.0 ± 4.6 years old) and 50 men (72.7 ± 8.5 years old) did two sets of ankle plantar flexor and dorsiflexor isokinetic tests at 30°/s. Peak torque, total work, and coefficient of variation were analyzed.Results: Men did the strongest plantarflexion torque (p < 0.05) and dorsiflexion torque (p < 0.05); their highest peak torque occurred at set 2 (p < 0.05), while the largest plantarflexion torque variability (p < 0.05), dorsiflexion torque variability (p < 0.05), and the largest plantarflexion torque variability occurred at set 1 (p < 0.05). Men did the highest plantarflexion and dorsiflexion total work (p < 0.05) at set 2 (p < 0.05).Conclusion: Older men are stronger than older women. The torque variability, in men, was higher during the first set, suggesting an adaptation to the isokinetics evaluation. Clinicians and researchers should consider that different muscles might need different numbers of sets and trials to measure their maximal muscle strength.